Reviving the Balance: The Authority of the Qurʼan and the Status of the Sunnah (Context: Journal of Interdisciplinary Studies, 2022)
Taha Džabir el-Alvani, Reviving the Balance: The Authority of the Qurʼan and the Status of the Sunnah. Herndon: Internacionalni institut za islamsku misao, 1438/2017. Str. 210. ISBN 978-1565646902.